2014
DOI: 10.1002/bimj.201200260
|View full text |Cite
|
Sign up to set email alerts
|

Structured additive regression modeling of age of menarche and menopause in a breast cancer screening program

Abstract: Breast cancer risk is believed to be associated with several reproductive factors, such as early menarche and late menopause. This study is based on the registries of the first time a woman enters the screening program, and presents a spatio-temporal analysis of the variables age of menarche and age of menopause along with other reproductive and socioeconomic factors. The database was provided by the Portuguese Cancer League (LPCC), a private nonprofit organization dealing with multiple issues related to oncol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 24 publications
5
24
0
Order By: Relevance
“…As a final remark, this study substantiated once again the decline of the age of menarche over time, as was observed in the univariate study presented by Duarte et al (2014). The negative effect achieved on the correlation, bringing into consonance the results observed for the age at menarche and a woman's reproductive lifespan cycle separately, proves the advantage of these models when modeling the effect of the covariates in the association between a bivariate response.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As a final remark, this study substantiated once again the decline of the age of menarche over time, as was observed in the univariate study presented by Duarte et al (2014). The negative effect achieved on the correlation, bringing into consonance the results observed for the age at menarche and a woman's reproductive lifespan cycle separately, proves the advantage of these models when modeling the effect of the covariates in the association between a bivariate response.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the results did not capture the expected spatial effect of earlier age of menarche and wider reproductive lifespan cycles associated with the coastal regions (Rodrigues, 1993;Duarte et al, 2014), not even for the younger women cohort. In particular, older women (born before 1931) showed a nonsignificant spatial effect on the expectation and on the standard deviation of the window.…”
Section: Figurementioning
confidence: 74%
See 2 more Smart Citations
“…20 Cheng found that BRCA 1452-1079 directly binds to WRN C-terminal region and subsequently lightly affects its functions. The most common polymorphisms of WRN Cys1367Arg are located in the binding domain of BRCA1.…”
Section: Discussionmentioning
confidence: 99%